INNOVATION PAI TEACHING THROUGH A CRITICAL APPROACH AT MUHAMMADIYAH 2 SENIOR HIGH SCHOOL SIDOARJO - Prawito, Anton; Tajdidul Islahi, Bilad; Mardiana, Dina (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the innovation of Islamic Religious Education (PAI) learning methods based on a critical thinking approach at SMA Muhammadiyah 2 Sidoarjo. The research employs a qualitative field research design to explore teachers’ and students’ experiences in implementing reflective, dialogical, and problem-based learning models. Data were collected through classroom observations, interviews, and documentation, and analyzed using Miles & Huberman’s interactive model. The findings reveal that critical-based PAI learning improves students’ participation, motivation, and critical reasoning while strengthening character and digital literacy. Teachers act as facilitators by applying discussion, case studies, and digital media integration, creating meaningful and contextual learning experiences. The study concludes that critical thinking approaches supported by technology and reflective pedagogy effectively foster 21st-century skills and Islamic character among students.